(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
article covers the information concerning various methods and approaches which aid to diminish the complexion of teaching English, specifically pronunciation activities. Easy and funny implementation of these task can be motivational guide for the teachers. Procedures and materials are also mentioned in this article.